Penanganan dan Penyimpanan Hasil Tangkapan Ikan di Kapal Pukat Cincin yang Berbasis di Pelabuhan Perikanan Samudera (PPS), Kendari - Iya Purnama Sari; Inzaghi Akbar Hidayat (Universitas Mataram, 2024)
The handling of fish catches in fishing activities is a very important initial handling and determines the quality of further fish. The handling fish on board while adhering to the guidelines for appropriate handling is very important and absolutely applied during and before fishing. This information indicates the importance of carrying out this research which aims to provide an overview of the techniques of handling and storing fish catches by paying attention to the principles of appropriate handling on board. This study was carried out from November 2023 - January 2024. The research used an incidental method, by selecting a fishing vessel with purse seine gear, namely KMN. Nurhikmah 02. Data collection used a purposive sampling method, the parameters studied included the feasibility of facilities and infrastructure for handling and storing fish catches on board. Next, the application of the process of handling and storing fish catches on board in accordance with the principles of handling. The data obtained are primary data from direct observation on the ship and secondary data through the interview process on the ship. The outcomes demonstrated that the types of fish caught on the ship included small and large pelagic fish groups with a total weight of fish catches reaching 13.65 tons of fish. The facilities and infrastructure used in handling are generally in decent condition, although rusty tools are still found. The application of the process of handling and storing fish catches on board has applied the principle of